Potencialidades e limites de uma s.d. sobre eugenia: educação para as relações étnico-raciais e controvérsias científicas - Miranda, Alexandre Marcel de (2022)
This work proposes a methodological approach to the development of a didactic sequence as an Educational Curriculum Material, having the controversial theme - Eugenics, which presents itself as a Socio-scientific Question - QSC. This theme is developed through three fields of Education: the Curriculum, Relations for Ethnic-Racial Education and Teacher Training. The proposition of this didactic sequence aligned with educational design and this triangulation of fields, in addition to presenting itself as an educational innovation, presents itself as a proposal to evaluate its potentialities and limitations. In this way, the work consisted in the formulation of criteria that, after analysis, bring the perception that the didactic sequence can, with its potential, reach the presupposed objectives and that, due to its limitations, the formation of the teacher is significantly a preponderant factor for the its existence. Therefore, when developing, in the future, the application and evaluation of this didactic sequence, it will be possible to guide the production of an Educational Curriculum Material (ECM), which is a curricular material that is concerned with the formation of the teacher, with the promotion of education on socio-scientific issues (QSC's), and more specifically, on education for ethnic-racial relations in Science Teaching.